Prostate cancer (metastatic) - Michaelson, M Dror (BMJ Publishing Group, 2003)
Prostate cancer metastasises predominantly to bone, which may cause pain, weakness, paralysis and death. Androgen deprivation Immediate androgen deprivation therapy may slightly improve 10 year survival compared with deferred therapy in men with advanced, asymptomatic prostate cancer, and may reduce the risk of major complications. Combined androgen blockade (androgen deprivation plus non-steroidal antiandrogen) may improve 5 year survival compared with androgen deprivation alone. We don't know whether intermittent androgen deprivation improves survival, morbidity or quality of life. Chemotherapy Newer chemotherapy agents (mitoxantrone, suramin) may improve symptoms but have not been shown to increase overall survival. Older chemotherapy agents have not been shown to be beneficial. External beam radiation may completely relieve pain in about a quarter of men with bone metastases, but no one regimen has been shown to be more effective than the others. Radionuclide therapy with strontium-89 may reduce the number of new sites of pain compared with placebo in men given external beam radiation, but its effect on survival is unclear. We don't know whether bisphosphonates improve symptoms or survival in men with metastatic prostate cancer, as few studies have been found.